The Merits and Challenges of Flipped English Grammar Learning Among Indonesian First-Year Undergraduate Non-ELT Students - Arif Husein Lubis; Risa Triarisanti; Sulaiman Sulaiman (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
Flipped learning has been considered a catalyst for teaching English grammar since it promotes active learning and higher-order thinking skills. Despite this potential, its implementation process in non-ELT classrooms has not received ample attention. This study seeks to examine the merits and challenges of implementing flipped learning in a grammar class for Indonesian first-year undergraduate non-ELT students majoring in Korean Language Education in an online learning environment. The students were divided into two groups (experimental group=35 students and control group=35 students). Using a quantitative and qualitative design, two grammar tests (pre- and post-tests) were administered to measure the effect of implementing flipped learning. A questionnaire was distributed to the students afterward, followed by interview sessions. While the quantitative data were analyzed using SPSS 23, the qualitative data were examined using an inductive thematic approach. The results showed that the implementation of the flipped learning approach could significantly enhance the students’ grammar skills. In addition, the students perceived that flipped learning could elevate learning motivation, foster learner autonomy, and raise learning awareness. However, lower motivation, an unconducive home environment during asynchronous sessions, and unstable internet bandwidth were the main challenges experienced by some students.